The Effect of Job Satisfaction and Organizational Commitment on Turnover Intention in Gen Z Employees on PT. SK - Rohendra, Titto; Fahlevi, Reza (Fakultas Ekonomi Universitas Garut, 2025)
The demographics of productive age employees in Indonesia are currently dominated by Gen Z or employees born in the 1995-2010 period. Research results in Indonesia state that Gen Z is known to have high turnover activity during the 2021 period, and the same is true at PT SKI. The results of pre-research at PT SKI and the results of Deloitte's global research state that Gen Z is very concerned about two things, namely Job Satisfaction & Organizational Commitment. Associative research using a quantitative technique is part of this study. 98 respondents who are Gen Z workers who are still employed by PT SKI participated in this study. Interviews, observations, and questionnaires are used in data collecting. Multiple and simple correlation are used in data analysis approaches. As indicated by a correlation coefficient value of 0.487, the research findings indicate that among Gen Z employees, job satisfaction and organizational commitment have a simultaneous impact on turnover intention in the category of moderate/sufficient degree of relationship.